Nature versus urban hiking for Veterans with post-traumatic stress disorder: a pilot randomised trial conducted in the Pacific Northwest USA - Littman, Alyson J; Bratman, Gregory N; Lehavot, Keren; Engel, Charles C; Fortney, John C; Peterson, Alexander; Jones, Alex; Klassen, Carolyn; Brandon, Joshua; Frumkin, Howard (BMJ open, 2021)
ObjectivesTo evaluate feasibility and acceptability of a group-based nature recreation intervention (nature hiking) and control condition (urban hiking) for military Veterans with post-traumatic stress disorder (PTSD).Design and settingA pilot randomised controlled trial conducted in the US Pacific Northwest.ParticipantsVeterans with PTSD due to any cause.InterventionsTwenty-six participants were randomised to a 12-week intervention involving either six nature hikes (n=13) or six urban hikes (n=13).Primary and secondary outcome measuresFeasibility was assessed based on recruitment, retention and attendance. Questionnaires and postintervention qualitative interviews were conducted to explore intervention acceptability. Questionnaires assessing acceptability and outcomes planned for the future trial (eg, PTSD symptoms) were collected at baseline, 6 weeks, 12 weeks (immediately after the final hike) and 24 weeks follow-up.ResultsOf 415 people assessed for eligibility/interest, 97 were interested and passed preliminary eligibility screening, and 26 were randomised. Mean completion of all questionnaires was 91% among those in the nature hiking group and 68% in those in the urban hiking group. Over the course of the intervention, participants in the nature and urban groups attended an average of 56% and 58%, respectively, of scheduled hikes. Acceptability of both urban and nature hikes was high; over 70% reported a positive rating (ie, good/excellent) for the study communication, as well as hike locations, distance and pace. Median PTSD symptom scores (PTSD Checklist-5) improved more at 12 weeks and 24 weeks among those in the nature versus urban hiking group.ConclusionsThis pilot study largely confirmed the feasibility and acceptability of nature hiking as a potential treatment for Veterans with PTSD. Adaptations will be needed to improve recruitment and increase hike attendance for a future randomised controlled trial to effectively test and isolate the ways in which nature contact, physical activity and social support conferred by the group impact outcomes.Trial registration numberNCT03997344.